Data processing method for constitutive relation of the rubber core material in spherical blowout preventer. (July 2018) - Xu, Daping; Yang, Yingxin; Wu, Kaisong
A data processing method for constitutive relation of large deformation rubber core in spherical blowout preventer is put forward in this article. Based on the Yeoh constitutive model and the large-deformation theory of rubber material, this article studied the constitutive relation of core material in blowout preventer. The constitutive relation experiments, the uniaxial tensile experiment, the uniaxial compression experiment, the plane tensile experiments, and the volume compression experiment were conducted and the corresponding experiment data were fitted, respectively, on basis of which the uniaxial compression data were selected for further study. For comparison, the data were, respectively, processed with a novel method and the method in GB/7757, and accordingly, two different constitutive relations were obtained and introduced into ABAQUS to simulate the experiment process. Research results show that the relative error of maximum axial deformation between the simulation using GB/7757 and the actual experiment is 34.7%, while that between the novel method and the actual experiment is 20.4%, having improved the accuracy by 14.3%, proving that the data processing method in this article can effectively improve the accuracy of finite element simulation for the core material and will contribute to the research on the performance of spherical blowout preventer.